Effect of calcium-alginate and essential oil on Colletotrichum acutatum and the shelf life of the grape - Dong, Lieu My; Quyen, Nguyen Thi Truc; Thao, Le Thi Thu; Thao, Tran Thi Thu; Quyen, Cu Thi Ngoc; Kim Thuy, Dang Thi (Vietnam Journal of Science and Technology, 2019)
The purpose